Species-specific functional interactions of DNA polymerase alpha-primase with simian virus 40 (SV40) T antigen require SV40 origin DNA. - Schneider, C (1994)
Physical and functional interactions of simian virus 40 (SV40) and polyomavirus large-T antigens with DNA polymerase alpha-primase were analyzed to elucidate the molecular basis for the species specificity of polymerase alpha-primase in viral DNA replication. SV40 T antigen associated more efficiently with polymerase alpha-primase in crude human extracts than in mouse extracts, while polyomavirus T antigen interacted preferentially with polymerase alpha-primase in mouse extracts. The apparent species specificity of complex formation was not observed when purified polymerase alpha-primases were substituted for the crude extracts. Several functional interactions between T antigen and purified polymerase alpha-primase, including stimulation of primer synthesis and primer elongation on M13 DNA in the presence or absence of the single-stranded DNA binding protein RP-A, also proved to be independent of the species from which polymerase alpha-primase had been purified. However, the human DNA polymerase alpha-primase was specifically required for primosome assembly and primer synthesis on SV40 origin DNA in the presence of T antigen and RP-A.